Eletromiografia de superfície dos músculos masseter e temporal em sujeitos com bruxismo - Almeida, Flavia Leães de (2009)
This study aimed to analyze the electric activity of masseter and temporal muscles, in subjects with bruxism. The specific objectives were to measure the electric activity of the masseter and temporal muscles, to verify the graduation of the pain to the palpation and your correlation with the electric activity in subjects with bruxism, and to compare the electrical activity pattern of these muscles in subjects with and without bruxism. 31 participants, male and female, aged between 19 and 51 years old were volunteers in the study, 20 of them with bruxism (SG) and 11 without bruxism (CG). The participants were examined based on RDC/TMD instrument, dentistry and speech pathology assessments and electromyography exam. The last one was carried out during rest, maximum intercuspation and the rhythmic mastication. The results showed that the electromyography pattern of the muscles was presented next to the levels to normality during rest, maximum intercuspation and usual mastication rhythmic in the subjects with and without bruxism. Most of the subjects presented complaint of pain, being more evidenced the severe degree and mainly in the muscle masseter. There was not statistically significant correlation between pain and EMG activity. It was not observed statistically significant differences in the studied muscles, except for the right masseter during the rest and for left masseter during the mastication when comparing the averages of the electric activity of the subjects with and without bruxism. It can be concluded that the pain did not consist a harmful factor to the electric activity performance of the studied muscles in the appraised situations and that the bruxism did not alter the electric activity of the masticatory muscles.